"Manarairema" e "Bacurau" : sobre visualidades, invasões e sobrevivências - Silva, Glauber Honorato da (2021)
Vision determines visual perception as a physical operation, and visuality assumes this perception as a social factor. In this case, visuality involves techniques, machines and discursive intentions of the cultural and visual experience (FOSTER, 1998). In these terms, what are the questions that establish visuality (visibility, vigilance, visualization) in The three trials of Manirema (1966) novel and in the Bacurau (2019) film? This is sort of the motivating inquiry of our discussion. As a first drive, this question ramifies itself in social, political and aesthetical matters by a methodology that comprehends images in their associative, comparative and allegoric relations. First, in The three trials of Manirema, we can observe the methods, practices and effects of the structural vigilance in modernity/coloniality from the panoptical example (BENTHAM, 2008), the disciplinary society studies (FOUCAULT, 1987) and the elucidations on Visuality (MIRZOEFF, 2016). Then, in Bacurau, we can see the reconfiguration of the vigilance’s possibilities in a perspective more related to decoloniality and transmodernity (DUSSEL, 2017), in which the mechanisms, practices, effects and intentions of watching and being watched do not limit themselves to the Foucauldian and Benthanian structural vigilance.